Studies on the diversity and growth of moulds in the cucumber pickle - HAPSARI SETIA PUTRI; SURANTO SURANTO; RATNA SETYANINGSIH (Biodiversitas Journal of Biological Diversity, 2003)
The aims of this research were to study about the growth and diversity of moulds in the cucumber pickle and the influencesof acetic acid concentration and long storage as well as additional of onion on the growth of moulds. Cucumber pickle was treated in different acetic acid concentrations (0,8%, 1,4%, 2,0%), long storage and with or without additional of onion. Theused method to isolate of mould was dilution planting. For enumerating moulds, 0,1 ml samples were blended and dilutedafter that inoculated on to potato sucrose agar (PSA) medium and then incubated at 270C for 7 days. To identify the moulds, the colony was transferred on to CDA and PSA media, and then incubated at 270C for 7 days. The moulds were identified according to their macroscopic and microscopic characters. To know the degrees of taste, the cucumber pickle was tested to 25 people with hedonic scale method. The results showed that, there was 12 different kinds of moulds can be found in cucumber pickle without additional of onion. There were Aspergillus fumigatus, A. niger, A. ochraceus, A. tamarii Kita, Cochliobolus sp, Botrytis, Penicillium chrysogenum, P. expansum, P. citrinum, Rhizopus oligosporus, Trichoderma sp,and Monilia. On the other hand, experiment with onion, P. expansum and A. niger could not be observed. The highestvarieties of moulds can be found in cucumber pickle with acetic acid concentration 1,4%. In experiment without onion, on nil(0) day, with acetic acid concentration of 1,4%, the amount of moulds is lower than in the pickle with acetic acid concentration 0,8%. The diversity of moulds in the cucumber pickle with additional of onion is lower than that of without onion. The additional of onion showed decreasing the diversity and growth of moulds in cucumber pickle with acetic acid concentration of 0,8% on nil (0) day. In experiment with acetic acid concentration 2,0% in 10-1 dilution on nil (0) day until 6thday, the moulds could not be observed.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKeywords: diversity, growth of moulds, cucumber pickle